La cooperación descentralizada española ante los retos de desarrollo del milenio - Illán Sailer, Carlos (Revista Española de Desarrollo y Cooperación, 2023)
Despite its weaknesess, the current spanish de-centralized cooperation system is taking relevant steps to improve the aid it delivers to developing countries while, at the same time, is steadily focusing on the Millenniumm Development Goals as the main framework from which to operate in coordination with other public and private actors. The article presents the main obstacles and opportunities if such an approach is to be set into motion.